Using Trust as a Resource for Social Value Creation: A Case of JanaJal. (August 2021) - Kulshrestha, Reeti; Sahay, Arunaditya; Sengupta, Subhanjan
Research question: With the help of an instrumental research case on a social enterprise in India that provides a solution to those with none or limited access to fresh drinking water, this study aims to explore how trust helps create social value. Links to theory: At the theoretical level, the study draws upon 'trust' and 'social value' literature to examine how a social entrepreneur utilized trust as an enabler to creating social value. Phenomenon studied: The case developed deeper understanding of the phenomena of 'trust helps creating social value'. Type of the case: It is an instrumental research case study that helps explore the phenomenon and draws connections between trust and social value creation if any. Case context: The case context is making affordable drinking water available to all, especially the community of people who are deprived of it. Findings: Conducting a series of in-depth interviews with the founder, we developed a better understanding of how the social entrepreneur used trust as a resource to create social value in the context of affordable drinking water. The findings showed how the protagonist (founder) worked on gaining trust of his beneficiaries and stakeholders to create social value. Findings also revealed the enablers and deterrents of trust in social value creation. Discussions: Our study shows how trust as a resource creates social value. In the context of our study, it contributes on how a social entrepreneur is creating social value not only by making affordable drinking water accessible to all but also deliver other social value creation benefits. The study brings out legitimacy, technology and social network as its enablers. The study also intends to fill the knowledge gap on how firms create social value by building trust with stakeholders and beneficiaries. Since little is known about trust even at the level of beneficiaries and stakeholders, our study aims to develop a better understanding of the phenomenon.